Side-chain engineering of conjugated polymers toward highly efficient near-infrared organic photo-detectors via morphology and dark current management. Issue 23 (12th May 2020) - Kang, Yeongkwon; Eun, Hyeong Ju; Kye, Hyojin; Kim, Dahee; Heo, Junseok; Kim, Jong H.; Kim, Bong-Gi
Abstract : A side-chain engineered conjugated polymer provides outstanding NIR detectivity exceeding 2.0 × 10 12 Jones, due to enhanced photo-responsivity and suppressed dark current. Abstract : A series of conjugated polymers (CPs) sharing the same conjugated framework were designed to investigate their detection capability of near infrared light (1000 nm). Through engineering of the CP side-chains, both the light harvesting efficiency and the degree of dark current, which are crucial parameters for determining the performance of photo-detectors, were intercorrelated with the miscibility of CP with n-type PC71 BM and the energy level configuration of the inverted-type device architecture. Based on the morphological analysis of the active layer, 2EO-PDBF, containing ethylene glycol units in the side-chain, was found to form enlarged CP:PC71 BM interfaces, resulting in superior photo-responsivity compared to other CPs bearing aliphatic side chains. In addition, it was verified that the relatively shallow lowest energy level (LUMO) of 2EO-PDBF suppressed the generation of dark current by serving as an energetic barrier against electron injection from the Ag electrode. Consequently, due to both the reduced dark current and ameliorated photocurrent in 2EO-PDBF compared to those of other CPs with the same conjugated framework, a superior photo-detectivity exceeding 2 × 10 12 Jones was attained at 1000 nm with a rapid response time (350 and 410 μs for the rise and decay times, respectively). The obtained results clearly provide plausible design strategies for CPs to limit the dark current and to improve the light harvesting efficiencies of organic photo-detectors.